3-Hydroxytyrosol regulates biofilm growth in Cunninghamella elegans. Issue 3 (March 2021) - Khan, Mohd Faheem; Murphy, Cormac D.
Abstract: In contrast to yeast biofilms, those of filamentous fungi are relatively poorly understood, in particular with respect to their regulation. Cunninghamella elegans is a filamentous fungus that is of biotechnological interest as it catabolises drugs and other xenobiotics in an analogous manner to animals; furthermore, it can grow as a biofilm enabling repeated batch biotransformations. Precisely how the fungus switches from planktonic to biofilm growth is unknown and the aim of this study was to shed light on the possible mechanism of biofilm regulation. In dimorphic yeasts, alcohols such as tyrosol and 2-phenylethanol are known to control the yeast-to-hypha switch, and a similar molecule might be involved in regulating biofilm in C. elegans . Gas chromatography-mass spectrometry analysis of crude ethyl acetate extracts from supernatants of 72 h planktonic and biofilm cultures revealed 3-hydroxytyrosol as a prominent metabolite. Further quantification revealed that the amounts of the compound in planktonic cultures were substantially higher (>10-fold) than in biofilm cultures. In the presence of exogenous 3-hydroxytyrosol the growth of aerial mycelium was inhibited, and there was selective inhibition of biofilm when it was added to culture medium. There was no biotransformation of the compound when it was added to 72 h-old cultures, in contrast to the related compounds tyrosol and 2-phenylethanol, which were oxidised to a number of products. Therefore, we propose that 3-hydroxytyrosol is a new signalling molecule in fungi, which regulates biofilm growth. Highlights: 3-Hydroxytyrosol is a novel signalling molecule to regulate fungal biofilm growth. Planktonic cultures have higher concentrations of the metabolite. Cunninghamella elegans biofilm growth is selectively inhibited by 3-hydroxytyrosol. 2-Phenylethanol and tyrosol inhibit planktonic and biofilm growth of C. elegans . 3-Hydroxytyrosol is not biotransformed by the fungus.